The History of the Church through 100 Masterpieces - Duquesne, Jacques, 1930- (Book collections on Project MUSE., 2011)
"Designed to highlight the deeper meanings in 100 paintings, reproduced here, that were inspired by events in Christian history; the authors provide brief descriptions of each painting to discuss both the historical events and the religious and cultural background surrounding them"--Provided by publisher.